Unitarian Universalist Church of Fresno "Love is a Magic Pony" and Cupcake Making - Watkins, Howard::::::::: (1988)
Saul Eskin and Adam Watkins peeling bananas as ? slice them; Marcy Spaulding setting out cupcake holders